2016
DOI: 10.1159/000445250
|View full text |Cite
|
Sign up to set email alerts
|

Bone Healing and Hormonal Bioassay in Patients with Long-Bone Fractures and Concomitant Head Injury

Abstract: Objective: The aim of this study is to investigate healing of fractures in patients with concomitant head injuries and to measure blood hormone levels to elucidate the mechanism of a possible accelerated osteogenesis. Materials and Methods: One hundred and sixty-two patients were included in this study and divided into 3 cohorts: group A with head injuries only (n = 52); group B with head injuries as well as long-bone fractures (n = 50); group C with long-bone fractures only (n = 60). Fracture-healing paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…The study also, showed statistically significant higher levels of growth factors of PDGF, VEGF, Activin-A, and cytokine I-L-1, along the 3 weeks of follow-up (P>0.005). I-IGF-II showed statistically significant subnormal level along the whole followup period in the same patients (P>0.005) [1,2].…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…The study also, showed statistically significant higher levels of growth factors of PDGF, VEGF, Activin-A, and cytokine I-L-1, along the 3 weeks of follow-up (P>0.005). I-IGF-II showed statistically significant subnormal level along the whole followup period in the same patients (P>0.005) [1,2].…”
mentioning
confidence: 74%
“…These sera were used as well, to investigate their effect on the growth of stem cell culture by measuring the cell count of cell line of human bone marrow-derived mesenchymal stem cells MSCs (ATCC-USA) treated with control and patients' sera from different groups after 72 hrs incubation [1,2].…”
mentioning
confidence: 99%
“…The mechanisms affecting fracture union after head trauma are still not fully understood. In a recent study, [16] it was claimed that the combination of relative inhibition of the sympathetic nervous system and non-hormonal mechanisms was effective. In the same study, parathyroid hormone levels peaked in the first 24 h in human serum samples from cases with head trauma and from cases who had head trauma accompanied by long bone fractures, and that both groups had higher values than the control group with isolated long bone fractures.…”
Section: Discussionmentioning
confidence: 99%
“…This assumption would also support the finding of the aforementioned experimental study that fracture fixation has more impact on fracture healing than concomitant injuries [ 23 ]. Another clinical study demonstrated shorter healing times, greater callus volumes and higher fracture healing rates in patients with concomitant TBI [ 25 ]. In contrast to our study, they included all long bones fractures (including humeral and fibular fractures) treated either with intramedullary nailing or plate osteosynthesis.…”
Section: Discussionmentioning
confidence: 99%